Implementing of the ISON project in Northern Mexico - Mokhnatkin, Artem; Molotov, Igor; Tijerina Perez, Eduardo Gerardo; Leon Perez, José Enrique; Kokina, Tatiana; Schildknecht, Thomas (2019)
Abstract:ISON,beinganopeninternationalprojectthatcollectsandinterpretsdataaboutspaceobjectsforscientific analysisandspacecraftoperators,includesabout40observationalsites.AninvolvementoftwoMexicansitesparticipatinginopticalobservationsofgeostationaryandhighlyellipticalobjectsasapartoftheISONprojectisconsidered. Abriefdescriptionofthefacilitiesandtheirobservationstatisticsaregiven.Prospectsforthefurtherdevelopmentof sitesformonitoringnear-EarthobjectsinMexicoarepresented,includingdataofastronomicalobservingconditions fromfieldstations. Keywords:telescope,highellipticalorbit,geosynchronousorbit,spacedebris,satellite,tracking